Direct analysis in real time: a critical review on DART-MS - Gross, Jürgen H. (Analytical and bioanalytical chemistry, 2014)
Direct analysis in real time mass spectrometry (DART-MS) has become an established technique for rapid mass spectral analysis of a large variety of samples. DART-MS is capable of analyzing the sample at atmospheric pressure, essentially in the open laboratory environment. DART-MS can be applied to compounds that have been deposited or adsorbed on to surfaces or that are being desorbed therefrom into the atmosphere. This makes DART-MS suitable and well-known for analysis of ingredients of plant materials, pesticide monitoring on vegetables, forensic and safety applications such as screening for traces of explosives, warfare agents, or illicit drugs on luggage, clothes, or bank notes, etc. DART can also be used for analysis of either solid or liquid bulk materials, as may be required in quality control, or to quickly investigate the identity of a compound from chemical synthesis. Even living organisms can be subjected to DART-MS. Driven by different needs in analytical practice, the combination of the DART ionization source and interface can be configured in multiple geometries and with various accessories to adapt the setup as required. Analysis by DART-MS relies on some sort of gas-phase ionization mechanism. In DART, initial generation of the ionizing species is by use of a corona discharge in a pure helium atmosphere which delivers excited helium atoms that, upon their release into the atmosphere, will initiate a cascade of gas-phase reactions. In the end, this results in reagent ions created from atmospheric water or (solvent) vapor in the vicinity of the surface subject to analysis where they effect a chemical ionization process. DART ionization processes may generate positive or negative ions, predominantly even-electron species, but odd-electron species do also occur. The prevailing process of analyte ion formation from a given sample is highly dependent on analyte properties.
Published online: 15 September 2013
Gesehen am 13.10.2020